Parental Burden and Quality of Life in 5q-SMA Diagnosed by Newborn Screening - Heike Kölbel; Laura Modler; Astrid Blaschek; Ulrike Schara-Schmidt; Katharina Vill; Oliver Schwartz; Wolfgang Müller-Felber (MDPI AG, 2022)
The aim of this study was to assess the psychosocial burden in parents of children with spinal muscular atrophy (SMA), detected by newborn screening (NBS), for which first pilot projects started in January 2018 in Germany. The survey, performed 1-2 years after children's diagnosis of SMA via NBS, included 3 parent-related questionnaires to evaluate the psychosocial burden, quality of life (QoL)/satisfaction and work productivity and activity impairment in the families. 42/44 families, detected between January 2018 and February 2020, could be investigated. Interestingly, statistical analysis revealed a significant difference between families with children that received SMN-targeted therapy vs. children with a wait-and-see strategy as to social burden (p = 0.016) and personal strain/worries about the future (p = 0.02). However, the evaluation of QoL showed no significant differences between treated vs. untreated children. Fathers of treated children felt more negative impact regarding their productivities at work (p = 0.005) and more negative effects on daily activities (p = 0.022) than fathers of untreated children. Thus, NBS in SMA has a psychosocial impact on families, not only in terms of diagnosis but especially in terms of treatment, and triggers concerns about the future, emphasizing the need for comprehensive multidisciplinary care. Understanding the parents' perspective allows genetic counselors and NBS programs to proactively develop a care plan for parents during the challenging time of uncertainty, anxiety, frustration, and fear of the unknown.